Serum Epidemiological Analysis and Risk Factors Associated with Leptospira spp. in Cattle in the State of Piauí - Ferreira, Siluana Benvindo; Sousa, Katiene Régia Silva; Castro, Vanessa; Lopes, Sabrina Thabla Pereira; Ferreira, Sávio Benvindo; Feitosa, Lauro César Soares; Moura, Ludmila de Moraes; Mineiro, Ana Lys Bezerra Barradas; Freitas, Daniela Reis Joaquim de; Souza, José Adalmir Torres de (Acta Scientiae Veterinariae, 2017)
Background: Leptospirosis is a cosmopolitan zoonosis caused by pathogenic spirochetes of the genus Leptospira spp. and it is considered one of the main causes of reproductive problems in cattle. Therefore, the aim of this study was to determine the occurrence of anti-Leptospira antibodies and identify the prevalent serovars and risk factors associated with infection in cattle herds, in the microregion of Floriano, Piaui State, Brazil. Materials, Methods & Results: A total of 414 bovine sera samples were collected (390 females aged over 24 months and 24 bulls) from 22 properties (farms) in the municipalities that compose the study area. The samples were analyzed using the Microscopic Agglutination Test (MAT) to detect anti-Leptospira antibodies from 23 pathogenic serovars. An epidemiological questionnaire was applied in each farm to evaluate the risk factors, using a univariate analysis of the variables of interest, by Pearson’s Chi-square test (χ2) or Fisher’s exact test, when it was necessary. Then, each independent variable was crossed with the dependent variable and those that presented statistical significance <0.20 were selected for multivariate analysis, using logistic regression, adopting a significance level of 5%. This research identified 143 positive animals (MAT> 1: 100) in the 22 evaluated farms; all of them had at least one positive animal, resulting in a prevalence of 34.54%, with 32,8% females (136) and 1,7% males (07), and 8,93% (37) of co-agglutination. Nineteen of the 23 tested serovars were identified; among them, Icterohaemorrhagiae (42.48%), Hardjo (31.2%), Pomona (4.3%), and Castellonis (4.3%) stood out. Absence of quarantine (OR = 16.172, P = 0.024), vaccination (OR = 0.090, P = 0.037) and isolation of diseased animals (OR = 0.006, P = 0.030) were identified, by the multivariate logistic regression analysis, as risk factors for any serovar of Leptospira spp. Discussion: The results of the present study showed that leptospirosis is present in all studied municipalities, in which the prevalence may be related to the variety of factors that influence the occurrence of the disease, such as climatic and environmental conditions, transit of animal, practices of management adopted in the herd, and the lack of information about the disease. The occurrence of co-agglutination can be explained by the possibility of multiple and concomitant contaminations with several serovars. Icterohaemorrhagiae was the most prevalent serovar, which has significant importance to public health since it is considered the main serovar of leptospirosis in humans, associated with the presence of rodents. On the other hand, the serovar Hardjo is related to the chronic leptospirosis in cattle, demonstrated through reproductive problems. The serovars Castellonis and Pomona were also observed in bovine herds, suggesting a possible transmission of the microorganism between animal species, probably due to exposure to the same sources of infection. In fact, the large number of serovarieties of Leptospira spp. indicates the presence of one or more maintenance hosts, which are natural reservoirs of this infection. The risk factors confirmed in the logistic regression analysis probably occur due to failures in sanitary management. It is concluded that Leptospira spp. is disseminated in cattle in the studied region, with the presence of several serovars, which reinforces the need for intensifying the prevention and control measures, such as vaccination.